Effects of combination of alcohol and Cinnamomum burmannii essential oil against Klebsiella pneumoniae resistance - Jennifer Anggraini Sasangka; Handi Suyono; Gladdy Lysias Waworuntu (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Alcohol-based antiseptics are widely used in the COVID-19 pandemic to prevent the transmission of infections, including bacterial infections. However, bacterial resistance to the alcohol-based antiseptics is begun reported. Klebsiella pneumonia resistance is one of the bacterial resistances that is prioritized by the WHO to be overcome. Cinnamomum burmannii essential oil, containing cinnamaldehyde and eugenol, was investigated for antimicrobial activity. This study aimed to evaluate the synergistic effect of the combination of alcohol and C. burmannii essential oil in inhibiting bacterial growth. Ethanol 80% in a combination with C. burmannii essential oil at concentrations of 1, 2, and 3% v/v were evaluated against K. pneumoniae using the Kirby-Bauer disc diffusion method. Test was repeated three times in independent experimental. Inhibition zone diameter (IZD, mm) and antimicrobial index (AI, %) were determined and analyzed using Kruskal-Wallis test continued the Mann-Whitney test. The combination of ethanol and C. burmannii essential oil was sensitive to K. pneumoniae, meanwhile, ethanol 80% was not more sensitive. The IZD of the combination solution at 1, 2, and 3% concentration were 6.7±0.19, 9.0±0.58, and 11.0±1.15mm, respectively (p<0.05). The AI of the combination solution at concentrations of 1, 2, and 3% v/v were 7.04±2.04, 30.53±6.79, and 51.64±12.91%, respectively (p<0.05). In conclusion, the combination of ethanol 80% and C. burmannii essential oil active against K. pneumoniae which resistant to the ethanol.